Repair and Strengthening of the Reinforced Concrete Lighting Pole using PCC and FRP Systems (Journal of Research Updates in Polymer Science, 2020)
This paper describes an unconventional case of the repair and strengthening of the lighting pole made of reinforced concrete using the Polymer Cement Concrete (PCC) and Fiber Reinforced Polymer (FPR) systems. The damage of the element as well as causes are discussed. The concept and technology of the repair and strengthening of the reinforced concrete lighting pole are presented in detail.